Economic Expertise In Leadership : How CEO Economic Certifications Drive Corporate EES Performance - Rosyadatul Ulufiyah; Iman Harymawan (Owner : Riset dan Jurnal Akuntansi, 2025)
This study examines the relationship between CEO economic certifications and corporate sustainability performance, particularly in environmental, economic, and social (EES) aspects. Using a dataset of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2021, the study applies Upper Echelons Theory to explore how CEO economic expertise influences strategic decision-making and corporate sustainability outcomes. The results show a significant positive correlation between CEO economic certification and EES Scores, suggesting that CEOs with economic backgrounds are more adept at implementing sustainability strategies, optimizing resource management, and improving corporate transparency. The findings also emphasize the increasing regulatory and market-driven expectations for corporate sustainability in Indonesia, particularly under frameworks such as POJK 51/2017. Despite the positive relationship, challenges remain in fully integrating sustainability principles across industries. The study provides implications for corporate governance, regulatory bodies, and investors seeking to enhance corporate sustainability through executive leadership.